Design of Android-Based Augmented Reality Physics Book for Grade XII of High School Chapter 9 Digital Technology - Elfisa; Safwan; Rizky Fadhillah (LPPM Politeknik Aceh Selatan, 2023)
Many senior high school students still rely on printed books for their learning, but these books often only provide 2D images with written explanations. This made Students difficult to fully ubnderstand the 3D nature of the images, especially in subjects like physic. To address this issue, the author developed an application using Augmented Reality (AR) Technology Which focused on Chapter IX of the physics textbook, mainly on